Lim Mah-Hui and Michael Heng Siam-Heng. COVID-19 and the Structural Crises of Our Time. Singapore: ISEAS - Yusof Ishak Institute, 2022. 199 pp. - Torres, Justine Nicole V. (Archīum Ateneo, 2022)
Excerpt from Book Review: Two years of living with the COVID-19 pandemic have made us acutely aware of symptoms. We have watched for changes in conditions that signal underlying problems, explored preventative measures, and intensely monitored the manifestations of the disease and the efficacy of remedies. In the Foreword to Lim and Heng’s work, Professor Andrew Sheng considers the pandemic as “probably the most devastating event of the twenty-first century” with control over a “microscopic virus” mirroring necessary controls on the macroscopic world (x). Indeed, Lim and Heng rightly examine the COVID-19 pandemic as itself a symptom of a deeper and more pervasive crisis with the many “structural and ideological weaknesses present and prevalent in a global free market economy run along neoliberal lines” (1).